Indicators for the Assessment of the Impact of Hydropeaking on Aquifers - Basilio Hazas, Mónica; Marcolini, G.; Wohlmuth, B.; Chiogna, Gabriele (Geophysical Research Letters, 2024)
The operation of hydropower plants leads to sudden changes in river stage and to a flow regime known as hydropeaking. Hydropeaking alters the morphology of the riverbed and water quality, and ultimately poses a risk to riverine ecosystems. While many indicators are available to quantitatively assess this problem in rivers, the impact of hydropeaking on aquifers is largely unknown and lacks of quantitative indicators. We analyze with wavelet techniques the spatial and temporal dynamics of surface water-groundwater interaction in an aquifer impacted by two differently regulated rivers. We propose four indicators to study the aquifer stress produced by hydropeaking and classify the observed groundwater head time series into weakly, moderately and highly impacted. This study opens the possibility for a quantitative assessment of the impact of hydropeaking on the groundwater ecosystem.
CRIS-Team Scopus Importer:2024-06-28
Keywords: groundwater; hydropeaking; hydropeaking indicators; surface water-groundwater interaction; wavelet analysis